Taxonomic significance of capsule and seed characters of Indian species of Murdannia Royle (Commelinaceae) - Antony, Ancy Attullil; Nampy, Santhosh (Phytotaxa, 2014)
Capsule and seed morphology of 26 species of Murdannia in India are studied using light microscopy and seeds of 23 species by scanning electron microscopy. The capsules show differences in size, shape and in the number and arrangement of seeds in the locules. The seeds also display considerable variation in size, shape, ornamentation, shape of hilum and position of embryotega. The present study provides useful characters for the delimitation of Indian species of Murdannia.